West Bengal's Approach to Fifth Five Year Plan (1974-79) - Planning Commission (Planning Commission, 1972)
The Planning process for the 5th plan was started with a Planning Commission document “Towards an Approach to the 5th Plan’’. The main points of departure of this Approach from past practices lie in emphasising the necessity of programmes for meeting the minimum needs of the people and for generating massive employment in addition to pursuing the programmes for normal development.
State Planning Board Government of West Bengal
State Planning Board Government of West Bengal